2007
DOI: 10.1021/bi700748y
|View full text |Cite
|
Sign up to set email alerts
|

Low-Light-Induced Formation of Semicrystalline Photosystem II Arrays in Higher Plant Chloroplasts

Abstract: Remodeling of photosynthetic machinery induced by growing spinach plants under low light intensities reveals an up-regulation of light-harvesting complexes and down-regulation of photosystem II and cytochrome b6f complexes in intact thylakoids and isolated grana membranes. The antenna size of PSII increased by 40-60% as estimated by fluorescence induction and LHCII/PSII stoichiometry. These low-light-induced changes in the protein composition were accompanied by the formation of ordered particle arrays in the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
72
0
2

Year Published

2011
2011
2022
2022

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 85 publications
(80 citation statements)
references
References 43 publications
6
72
0
2
Order By: Relevance
“…The density of the PSII complexes within each of the two membrane layers encasing the lumen is very high, averaging at 1,630 complexes per square micrometer. This value is within 5% of that determined from a freeze-fracture EM analysis of untreated (nonsolubilized) thylakoid membranes, which yielded a density of 1,720 complexes per square micrometer (19). An immediate consequence of the high PSII density is that the orientation of the oval contoured OEC complexes (Fig.…”
Section: Resultssupporting
confidence: 72%
“…The density of the PSII complexes within each of the two membrane layers encasing the lumen is very high, averaging at 1,630 complexes per square micrometer. This value is within 5% of that determined from a freeze-fracture EM analysis of untreated (nonsolubilized) thylakoid membranes, which yielded a density of 1,720 complexes per square micrometer (19). An immediate consequence of the high PSII density is that the orientation of the oval contoured OEC complexes (Fig.…”
Section: Resultssupporting
confidence: 72%
“…the supramolecular level. A well known phenomenon is that increasing the light intensity leads to alterations of the LHC/electron transport complexes ratio [56,57]. Under high light intensity, the abundance of LHCII decreases, whereas the amount of PSII and cytochrome b 6 f complexes increases.…”
Section: High-light-induced Changes In Supramolecular Protein Organizmentioning
confidence: 99%
“…The issue is complicated by the fact that the membrane is flexible and dynamic and able to respond to changes in environmental and growth conditions apparently by changing not only the composition but also the organization of the PSII supercomplexes [154][155][156]. It has been shown that part of the grana membrane is occupied by PSII arrays composed of supercomplexes with different antenna sizes (see above), but the abundance of the arrays seems to depend on the species analysed and on the growth conditions [134,135,149,157]. It is generally accepted that only part of the PSII supercomplexes is embedded in these regular arrays, while another part is present in the membrane in a less organized fashion.…”
Section: Psii Organization In the Grana Membranesmentioning
confidence: 99%
“…It is not clear what the role of the arrays is. It has been suggested that they facilitate the diffusion of small molecules [157] like plastoquinone, but it has also been suggested that they have the opposite effect of slowing down the diffusion [139] in the membrane.…”
Section: Psii Organization In the Grana Membranesmentioning
confidence: 99%